Enhancement of the mechanical properties of lightweight oil palm shell concrete using rice husk ash and manufactured sand - Foong, K.Y.; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Mo, K.H. (Springer Verlag (Germany), 2015)
This study explores the use of rice husk ash (RHA) and manufactured sand (M-sand) as replacements for cement and fine aggregate, respectively, in lightweight oil palm shell concrete (OPSC). In the first stage of this study, the effect of various cement replacement levels, with RHA (5, 10, 15, and 20) and 100 sand replacement with M-sand and quarry dust (QD), on the compressive strength of OPSC was investigated. The results showed that the highest compressive strength of OPSC of about 51.49 MPa was achieved with the use of 15 RHA and M-sand. In the second stage of the work, the variables of RHA (0 and 15) and M-sand (0, 50, and 100) were used to investigate their combined effects on the mechanical properties of OPSC. It was found that the combination of 15 RHA and 100 M-sand gave the best performance of OPSC in terms of mechanical properties, such as compressive, splitting tensile, flexural strength, and Young's modulus.